Chris Petersen for City Council Fundraiser at Butler Hall Park - Watkins, Howard::::::::: (1985)
Karen Humphrey and Chris Petersen wearing "3 to 4 FOREVERMORE" T-shirts with Les Kimber in middle wearing 3-piece suit